Penerapan Kurikulum Merdeka pada Pembelajaran Bahasa Indonesia Teks Laporan Hasil Observasi di Kelas VIII SMP Negeri 4 Gunung Talang - Ikhwatul khairiyah; Tressyalina Tressyalina (ALSYS, 2026)
The implementation of the Kurikulum Merdeka in Indonesian language learning is crucial for enhancing students’ literacy and critical thinking skills, yet studies that specifically examine the alignment of planning, implementation, and assessment in teaching Observation Report (Laporan Hasil Observasi, LHO) texts at the junior secondary level remain limited. This study aimed to analyze the implementation of the Kurikulum Merdeka in teaching LHO texts to Grade VIII students at SMP Negeri 4 Gunung Talang. A qualitative approach with a case study design was employed, involving two Grade VIII Indonesian language teachers, the vice-principal for curriculum, and the principal, selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis of lesson plans and instructional materials, and were analyzed using the Miles and Huberman model, which comprises data reduction, data display, and conclusion drawing. The findings show that the implementation of the Kurikulum Merdeka has been carried out well in terms of lesson planning, instructional practices, and assessment. Teachers have developed learning documents in the form of Learning Outcomes, Learning Objectives, Learning Objectives Sequences, and teaching modules in accordance with Kurikulum Merdeka guidelines. Instructional activities were conducted through group discussions and LHO text writing projects, although differences in student engagement levels were observed across classes. Assessment practices have included diagnostic, formative, and summative assessments; however, the documentation of diagnostic assessment and the provision of formative feedback still need to be strengthened. These findings deepen understanding of Kurikulum Merdeka implementation in Indonesian language instruction of LHO texts and provide a basis for reinforcing differentiated teaching practices and continuous assessment at the junior secondary school level.